2016
DOI: 10.12928/telkomnika.v14i3.3150
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Retweet Prediction Approaches: The Superiority of Random Forest Learning Method

Abstract: We consider the following retweet prediction task: given a tweet, predict whether it will be retweeted. In Keywords: retweet prediction, machine learning algorithms, performanceCopyright © 2016 Universitas Ahmad Dahlan. All rights reserved. IntroductionSocial media like Twitter has provided a platform for spreading information among users [1,2]. In this work we focus on the retweet prediction problem. Given a tweet, we would like to predict whether it will be retweeted. Applications of this task are, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
8
0
4
Order By: Relevance
“…The experiments have been compared by using the AUC (area under the precisionrecall curve) demonstrating the dependency of the model with respect to the user feature (e.g., followers counts), hashtag used popularity, user network features. Bunyamin and Tunys [9], have provided a comparison of the performance for different learning methods and features, in terms of retweet prediction accuracy and feature importance, to understand what kind of tweets would be retweeted, by using as response variable a dummy variable representing the two states of being retweeted or not retweeted. They have found that Random Forests method archives the best performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments have been compared by using the AUC (area under the precisionrecall curve) demonstrating the dependency of the model with respect to the user feature (e.g., followers counts), hashtag used popularity, user network features. Bunyamin and Tunys [9], have provided a comparison of the performance for different learning methods and features, in terms of retweet prediction accuracy and feature importance, to understand what kind of tweets would be retweeted, by using as response variable a dummy variable representing the two states of being retweeted or not retweeted. They have found that Random Forests method archives the best performance.…”
Section: Related Workmentioning
confidence: 99%
“…A part of the identified metrics has been also used in [55], where a simple descriptive and Principal Component Analysis have been provided without deriving a predictive model. In the paper of Bunyamin and Tunys [9], a comparative analysis of several methods has been proposed without considering all metrics we identified, and without addressing the prediction of the degree of retweeting.…”
Section: Identification Of Potential Features/metricsmentioning
confidence: 99%
“…The propagation of information in micro blogs has brought phenomenal enhancement and has accelerated inter-personal communication. Re-tweet mechanism gives an approach to enable social clients to hold the most recent news and help undertakings to do advertising on social-media stage [2]. Along these lines, it is of extraordinary practical importance to examine and investigate the re-tweet practices for improving the data spread and user involvement in micro blogs.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [7] melakukan prediksi dalam perspektif twitter individu dan mencoba melakukan prediksi dengan metode decision tree, regresi logistik dan support vector machine (SVM) [7]. Metode pembelajaran random forest telah diujikan dalam penelitian sebelumnya dan menunjukan hasil yang lebih baik dibanding metode yang sebelumnya diuji [8][9] [10].…”
unclassified
“…Bunyamin [8] dalam deteksi popularitas menemukan metode pelatihan yang memiliki performa terbaik adalah random forest dengan memanfaatkan fitur pengguna dan fitur konten. Dalam pencarian feature importance digunakan metode mean decrease importance (MDI) pada random forest dan recursive feature elimination (RFE) pada pelatihan regresi logistik, lalu nilai kepentingannya diurutkan.…”
unclassified